On the Interpretation of the Image in the Central Part of the Apse Decoration of the Church of the Mother of God of Kintsvisi Monastery (Georgia): Historiographical Aspect - Tatarchenko, Svetlana N. (Actual Problems of Theory and History of Art, 2013)
The wall paintings in the apse of the Church of the Mother of God of Kintsvisi Monastery (Georgia) have a rare iconographic program. The image in the central part of the apse decoration deserves a special notice. This article examines two interpretations of this image proposed by the researchers T. Velmans and M. Radujko (M. Радуjко).
Keywords: medieval Georgian art; Kintsvisi; 13th century; liturgical theme in Byzantine art; apse decoration